EP 4. Long term recordings of deep brain activity from the subthalamic nucleus in PD patients using PC+S. Issue 9 (September 2016) - Staub, F.; Neumann, W.-J.; Horn, A.; Schanda, J.; Schneider, G.-H.; Brown, P.; Kühn, A.
Abstract : Introduction: Oscillatory activity in the beta frequency band has been consistently found in the basal ganglia of patients with Parkinson's disease (PD) and was related to bradykinesia and rigidity. Therefore, it has been suggested as a potential biomarker for closed-loop deep brain stimulation in PD. However, so far deep brain recordings have been feasible only for a short time window during electrode implantation before the leads are connected to the pulse generator. More recently, local field potential (LFP) neuronal activity can be recorded by using a chronically implanted pulse generator (Activa PC+S; Medtronic). Objectives: To investigate stability of oscillatory activity in the beta frequency band in PD patients over a period of 8 months post implantation of a pulse generator device, -a prerequisite for its usability as future biomarker for closed-loop stimulation. Patients & methods: Recordings from two contact pairs (E1E2, E2E3) of 12 PD patients (4 female, 8 male patients; mean age at implantation: 63.2 years; range 56–72 years) who received the Activa PC+S device for deep brain stimulation (DBS) therapy were included in the study. Rest recordings were conducted using the chronically implanted pulse generator under ON and OFF medication condition at Baseline, 3 months and 8 months post implantation. Channels were not used for stimulation at the time of LFP recordings. UPDRS was obtained for all patients at each time point. Analysis was performed using fast Fourier transform based methods. Beta power was calculated as percentage relative spectral power separately for ON/OFF condition. For further visualization of beta peaks across all subjects we realigned the individual peak frequency in the range of −5 Hz to +10 Hz before averaging. Moreover peak power was correlated with UPDRS motor scores. Results: Power spectra averaged across all contacts in all subjects showed distinct peaks in the beta band at 3 and 8 months follow up but not at baseline. This was partly due to a wide spread of peaks within the 13–35 Hz band. Following peak realignment the peak amplitude of the beta peak OFF medication was similar for all three time points ( p > 0.3) and was significantly suppressed by levodopa medication ( p < 0.001). Moreover, beta peak power OFF medication correlated with individual UPDRS-III scores across time ( r = 0.47, p = 0.0017). Conclusion: Our study shows that oscillatory activity in the beta frequency band can be recorded chronically via the implanted pulse generator and beta power remains stable over a time period of 8 months of DBS (albeit a partial initial suppression or frequency dispersion that might be due to the stun effect). Moreover, a significant suppression of beta activity by antiparkinsonian medication could also be shown months after electrode implantation.